α-fluoro-β-alanine functions as a β-arrestin1-biased ligand of S1PR2 to upregulate DPD expression in cancer cells - Mingyong Tan; Hanbing Shao; Xinan Zhang; Yuyao Cheng; Zhimeng Sun; Ming Yang; Siyuan Mu; Weishi Liang; Bo Han; Xinfeng Wu; Xiaohui Liu; Yong Hai; et al. (Proceedings of the National Academy of Sciences, 2026)
α-fluoro-β-alanine (FBAL), a catabolite of the chemotherapeutic agent 5-fluorouracil (5-FU), has attracted significant attention due to its cardiotoxicity and neurotoxicity. However, its association with 5-FU resistance, a major obstacle in cancer treatment, has rarely been reported. In this study, FBAL was identified as a β-arrestin1-biased ligand of sphingosine 1-phosphate receptor 2 (S1PR2), which upregulates dihydropyrimidine dehydrogenase (DPD) expression and drives 5-FU resistance in colorectal cancer. Mechanistically, following exposure to FBAL, S1PR2, a G protein–coupled receptor (GPCR), is phosphorylated by recruiting G protein–coupled receptor kinase 6 (GRK6). Phosphorylated S1PR2 coupled with β-arrestin1, but not G proteins, to activate the MEK/ERK/AP-1 pathway and promote DPYD transcription. Ser343 was identified as the key phosphorylation site of S1PR2 using IP-MS analysis. This residue within the C-terminal domain mediates receptor interaction with β-arrestin-1 to activate the β-arrestin-1-dependent ERK pathway, as was confirmed in HCT116 S1PR2KO-ΔC cells and HCT116 S1PR2KO-S343A cells. In vivo , mice bearing orthotopic xenografts of HCT116 S1PR2KO-S343A cells exhibited significantly enhanced higher sensitivity to 5-FU treatment compared to those HCT116 S1PR2KO-WT cells following FBAL. Taken together, this study showed that exposure to FBAL induces S1PR2 phosphorylation at Ser343 within the C-terminal mediated by GRK6, activating the β-arrestin1-dependent ERK pathway to upregulate DPD expression. This study not only delineates a phosphorylation-dependent signaling pathway in chemoresistance but also establishes S1PR2 as a promising therapeutic target for overcoming 5-FU resistance in cancer.